2003
DOI: 10.1159/000072942
|View full text |Cite
|
Sign up to set email alerts
|

Tension-Free Vaginal Tape Procedure: An Effective Minimally Invasive Operation for the Treatment of Recurrent Stress Urinary Incontinence?

Abstract: The aim of this study was to evaluate the results of tension-free vaginal tape (TVT) surgery in women with recurrent stress urinary incontinence (SUI). Fifty-one women with recurrent SUI were treated with TVT and followed prospectively for a minimum of 2 years according to a protocol. Twenty percent of the women had already undergone two previous continence procedures, whereas 80% had undergone only one. The mean follow-up period was 25.3 months. The objective cure rate was 89.6%, and the subjective cure rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
2

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 27 publications
2
18
0
2
Order By: Relevance
“…1 summarises the flow for study selection in this systematic review. There was 1 RCT [4] and 11 prospective studies [5][6][7][8][9][10][11][12][13][14][15] with a total of 430 participants between 23 and 87 years of age (see Table 1 for details of included studies). There were nine non-comparative studies, eight of which described effectiveness of TVT and one used TOT (see Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 summarises the flow for study selection in this systematic review. There was 1 RCT [4] and 11 prospective studies [5][6][7][8][9][10][11][12][13][14][15] with a total of 430 participants between 23 and 87 years of age (see Table 1 for details of included studies). There were nine non-comparative studies, eight of which described effectiveness of TVT and one used TOT (see Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The interval between primary and repeat surgery ranged from 6 weeks to 48 months. Previous surgery included Burch colposuspension, Kelly plication, Marshall-MarchettiKrantz procedure (MMK), Stamey needle suspension, Pereyra's operation, MUS, conventional slings and paraurethral collagen injection in eight studies [4][5][6][7][8][9][10][11], while four studies [12][13][14][15] included women with previous failed MUS only.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the TVT procedure is well documented, including high success rates in primary [3], recurrent [4], and mixed [5] incontinence cases. Long-term results are good [6] and registries showing low rates of complications have been established [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…We consider it important to report our experiences despite the small number and the mixed outcome as there is no clear guidance on which approach would offer the best outcome. This is a non-comparative study; Kuuva 28 has found equally good findings with the classical TVT procedure in 51 patients with recurrent stress incontinence. The objective and subjective cure rate was 90 and 80%, respectively.…”
mentioning
confidence: 84%